Representações sociais: a historicidade do psicossocial - Lúcia Pintor Santiso Villas Bôas (Revista Diálogo Educacional, 2014)
This article aims to emphasize the historicity of social representations as a fundamental aspect for understanding the reappropriations processes, in contemporary society, of his- torically consolidated meanings. Because of this, it considers that social representations are the result, on one hand, of the reappropriation of contents coming from different chronological periods and, on the other hand, those generated by new contexts. In this perspective, the article briefly discusses some issues relating to the group’s history, mem- ory, structural and contents aspects of representations, in order to reveal the complexity of the historical dimension of social representations. The article ends with a survey that illustrates the possibilities for an analysis in this dimension.